Synthesis, crystal structure and properties of SmBaCo2-xFexO5+delta - Volkova, N. E.
The solid solution formation range in the SmBaCo2-xFexO5+delta (0 <= x <= 2) system examined at 1100 degrees C in air corresponds to 0 <= x <= 1.1. The crystal structure of SmBaCo2-xFexO5+delta with x <= 0.5 was described as orthorhombic (space group Pmmm), and with 0.6 <= x <= 1.1-as tetragonal (P4/mmm). The introduction of iron into the cobalt sublattice leads to a gradual increase of the unit cell parameters and volume, accompanied with increasing oxygen content determined by thermogravimetry. The dilatometric curves collected at 25-1100 degrees C in air exhibit moderate nonlinearities associated with the orthorhombic -> tetragonal phase transition, as confirmed by the high-temperature X-ray diffraction analysis. Temperature dependencies of the electrical conductivity measured by 4-probe dc method in the temperature range 25-1000 degrees C in air display maxima at 300-350 degrees C, whilst the conductivity decreases with iron additions. These trends were discussed in terms of the defect structure and nature of the main charge carriers in SmBaCo2-xFexO5+delta. It was also shown that SmBaCo2-xFexO5+delta is chemically stable with respect to the Ce0.8Sm0.2O1.9 solid electrolyte up to 1100 degrees C, but reacts with Zr0.85Y0.15O1.93 even at 900 degrees C. (C) 2013 Elsevier Inc. All rights reserved.